Ethical issues in nursing: a pilot study - Lemonidou, Chryssoula; Kiranou, M; Leino-Kilpi, Helena; Välimäki, Maritta; Dassen, Theo; Gasull, Maria; Scott, Philomena Anne; Arndt, Marianne; Παναγιώτου, Α; Merkouris, Anastasios (My University, 2001)
Purpose: 1. To investigate the elderly and surgical patients' and mothers' and the corresponding nursing personnel's point of view about the concepts of autonomy, privacy and informed consent. 2. To develop an instrument for measuring patients' and nurses' perceptions on the implementation of these concepts in clinical practice. The study is a part of the project funded (1998-2001) by European Commission (BMH4-98-3555) and it is conducted in five European countries: Finland (coordinator), Germany, Greece, Spain, and UK. Methods: An extensive literature review was made for the content development of the tool followed by the quantification stage and the pilot study in 70 patients and mothers and 80 nurses in general and long term care institutions in Athens. Two parallel questionnaires were distributed for data collection. Results: The majority of patients and nurses were women. Concerning the definitions of the concepts 59% of the patients and 28% of the nurses did not answer at all or stated ignorance about informed consent (56% of the patients and 47% of the nurses about autonomy, and 46% of the patients and 47% of the nurses about privacy). Both groups found the questions very extended and difficult to comprehend, and most of the subjects did not relate the concepts to nursing interventions. Alpha values ranged for the patients' questionnaire from 0.76 to 0.84 and for the nurses' from 0.82 to 0.86. Conclusion: Both patients and nurses could not define the concepts and neither they relate them to nursing interventions. This indicates the need to enhance ethical knowledge base for nurses.